Diabetic Myonecrosis: Rare Complication of a Common Disease (BIRDEM Medical Journal, 2018)
We report a case of sudden left thigh pain in adductor muscles of medial compartment, known as diabetic myonecrosis, in a 50-year-old patient with poorly controlled diabetes mellitus. Diabetic muscle infarction is a rare end-organ complication seen in patients with poor glycemic control and advanced chronic microvascular complications. Proposed mechanisms involve atherosclerotic microvascular occlusion, ischemia-reperfusion related injury, vasculitis with microthrombi formation, and an acquired antiphospholipid syndrome. The clinical presentation is swelling, pain, and tenderness of the involved muscle, most commonly the thigh muscles. Management consists of conservative measures including analgesia and rest.Birdem Med J 2018; 8(3): 263-265